Enhancing Santri Digital Literacy through English News Blogging Training: A Community Empowerment Program at Pondok Pesantren Al-Mansyuriyah, Tangerang - Gufron Gufron; Dwi Sloria Suharti; Tatu Zakiyatun Nufus; Ade Mahmud (CV Firmos, 2026)
This community service article reports an English news blogging training program designed to strengthen santri’s digital literacy and English news-writing skills at Pondok Pesantren Al-Mansyuriyah, Tangerang. The program aimed to improve participants’ understanding of responsible digital media use, basic journalistic writing, and blog-based publication. A descriptive qualitative community service approach was applied with 50 senior high school-level santri as participants. The training was conducted in three sessions, consisting of preparation, interactive lectures, discussions, guided English news-writing practice, blog introduction, publication assistance, and reflection. Data were collected through facilitator observation, participant responses, writing practice, and institutional feedback. The results show that participants produced several English news drafts and published several blog-based articles related to pesantren activities. Participants demonstrated improved understanding of news structure, 5W1H elements, digital ethics, and responsible content sharing. The program also encouraged santri interest in writing and provided an additional digital publication medium for pesantren activities. However, the limited duration restricted deeper mentoring in writing revision and blog management. Future programs should provide longer mentoring, structured assessment, and an English blogging club to sustain students’ writing practice and digital publication skills.